Iris Murdoch's Secular Theology of Culture - Antonaccio, Maria (Literature and theology, 2004)
This article argues that Iris Murdoch makes a distinctive contribution to the agenda of theological humanism by formulating a revised theology of culture. Specifically, the article claims that Murdoch provides a compelling apologia for religious life in a secular world in two ways: by defending the significance of individual consciousness, and by retrieving an idea of the religious depth of morality. In doing so, Murdoch's work challenges antihumanist currents in modern and postmodern thought, offers an alternative to confessional forms of religious reflection, and revises previous theologies of culture (such as Tillich's) by giving priority to the ethical dimension of human life.